SOCIO-ECONOMIC STATUS ITS INFLUENCE ON ACADEMIC INTEREST OF SECONDARY SCHOOL STUDENTS IN MEGHALAYA: A QUALITATIVE STUDY - Lamare, Toba; Myrthong, Euodia (Journal of Education Culture and Society, 2020)
Aim. The study intends to determine the influence of socio-economic status on academic interest of secondary school students in Meghalaya. The study was conducted in two districts of Meghalaya i.e., in East Jaintia Hills and West Jaintia Hills Districts. Method. The researcher used sequential explanatory design for collecting the necessary information. The procedure of data collection was that the researcher constructed a semi-structured interview schedule whereby it was validated by the experts in the field of education. In order to determine the influence of socio-economic status on academic interest of secondary school students, the researcher conducted an in-depth interview on 50 secondary school students who were studying in class X. These students were selected purposively from two districts of Meghalaya. The interview was conducted at school premises and the necessary information collected from students was recorded and transcribed to obtain the results. Results. Based on the interview conducted, the study found that socio-economic status did not influence the academic interest of the secondary school students; however, student’s high aspirations, their interest in various subjects, their ambitions, determination and will power to work hard in their studies influence their academic interest. Conclusion. Socio-economic status was not found to have influences on the academic interest of the secondary school students and on the whole the present study suggested for teachers and parents to work cooperatively in order to help students realize their goals and desires.